THE IMPACT OF RECENT FINANCIAL CRISIS ON THE HOTEL AND RESTAURANT INDUSTRY IN THE U.K. - Mishra, Rajdeep (2013)
The Global Financial Crisis of 2007-2008 has had an impact on various countries worldwide.UK has also been affected by it. Various businesses and commercial establishments have experienced tough times and have faced reduction in the commercial activity up to the extent of business closure. It has been argued that Tourism Industry is one of the worst affected in the recent financial crisis. Hotel and Restaurant Industry is not an exception as it is directly influenced by the Tourism. The study aims to find out how the recent financial crisis has impacted the Restaurant and Hotel Sector of British Economy. The Challenges it faced and how it has been able to cope up with the Economic climate.Various leading Hotel and Restaurant companies of the United Kingdom were randomly selected and their Financial Statements were analysed before and after the beginning of the financial crisis in the UK. The study aims to examine the key financial ratios for all the companies under consideration. The focus will be on finding out how the financial performance of the firms has been affected by the